Equipping Teachers to Adapt: A Look into Teachers’ Professional Development Programs in Times of COVID-19 Pandemic - M. Jackaria, Potchong; G. Caballes, Dennis (International Journal of Humanities and Education Development (IJHED), 2022)
This study was conducted to determine public school teachers' experiences and perspectives on different professional development programs during the COVID-19 pandemic. It also aimed at determining teachers’ motivation and barriers in attending TPDs. A multi-faceted survey questionnaire was given to 84 teacher-respondents representing 10 public schools in Tandubas District, Tawi-Tawi, the southernmost province of the Philippines. Prior to this, the questionnaire had undergone validation and reliability testing. Afterward, follow-up interviews were also made with ten selected teacher-respondents for an in-depth appreciation of the context of the data gathered. The result shows that teachers shifted to online courses and webinars during the pandemic. There is also a high frequency of utilization of informal professional development programs such as peer tutoring, coaching, and school-based Learning Action Cell (LAC) sessions. Other professional development programs such as formal degrees, reading of professional papers, professional networking, school and classroom observations, conducting education research, and attending conferences were least attended. In terms of topics, most teachers have attended training on students' assessment, module development, school readiness, and safety. The study also found a Significant difference in the professional development experiences of teachers of different educational backgrounds and schools. This means that teachers with higher education tend to avail themselves more and school culture is one factor that encourages teachers to attend professional development programs. The result also shows that most of the teachers joined various TPDs because of the desire to improve their teaching, encouragement from school heads and peers, and usefulness for a job promotion. As to the barriers, most of the teachers mentioned financial constraints, time constraints, and poor internet connectivity as the top three reasons for not attending professional development programs in the past 12 months.